If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + -14 + 3x + -2 = 6x Reorder the terms: -14 + -2 + 19x + 3x = 6x Combine like terms: -14 + -2 = -16 -16 + 19x + 3x = 6x Combine like terms: 19x + 3x = 22x -16 + 22x = 6x Solving -16 + 22x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -16 + 22x + -6x = 6x + -6x Combine like terms: 22x + -6x = 16x -16 + 16x = 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 16x = 0 Add '16' to each side of the equation. -16 + 16 + 16x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 16x = 0 + 16 16x = 0 + 16 Combine like terms: 0 + 16 = 16 16x = 16 Divide each side by '16'. x = 1 Simplifying x = 1
| -9y+4=-2y+24 | | 2+-8(x+8)=-26 | | 10x=3x^2+8 | | 5n^2+40n+75=0 | | -25=5v-5 | | 3x+5=-54 | | (3y+6)(3y-6)= | | 2p+5q=53 | | 10x=3x*2+8 | | 3(4x-7)=4x+15 | | y=10x-8 | | 29-9n=4n+3 | | 7p+9q=22 | | (4c-1)(5c-3)= | | 87+2x=5x | | 2y-3+4x=45 | | 6(p-1)-p=-2(p+1)+p-1 | | 6s-2=4s+6 | | 18=m-6 | | 4(x-1)+2(2x-3)=12-x+3(3-x) | | 4y-6x=36 | | 11x^2-4x+2=0 | | 4x+1=9x-20 | | 2ac^2+ac=b^2+3b | | 2(x-8)-(x-4)=3(x+5)+3 | | b^2+3b=4b^2 | | 3r+10=5r+2 | | 0.273y-18.3=.36-2.7y | | X^2-28=12x | | 0.723y-183=0.36-2.7y | | x^2+49y^2=0 | | x+4/4-2x-1/2=x-2/4 |